Effects of cervical stabilisation exercises on respiratory strength in chronic neck pain patients with forward head posture - Arif, Tooba; Rehman, Syed Shakil Ur; Ikram, Mehwish (Journal of the Pakistan Medical Association, 2022)
The objective of this study was to determine the effects of cervical stabilisation exercises on respiratory strength in chronic neck pain patients with forward head posture. The study was conducted from August 2020 to February 2021, at the Jinnah Hospital, Lahore; 44 patients who fulfilled the eligibility criteria were randomly assigned to two groups—experimental group and control group—. Baseline measurement was taken for numeric pain rating scale, neck disability index, craniovertebral angle, single breath count, and spirometry and all the measurements were retaken at the completion of the fourth week. Results were not significant (p>0.05) before the treatment in both groups but post-intervention results revealed significant differences in both the groups (p<0.05), with the experimental group showing more improvement. Four weeks of cervical stabilisation with isometric exercises is more effective in the management of pain, forward head posture, neck disability and respiratory strength as compared with the four weeks of isometric exercises programme alone. Keywords: Stabilisation, neck pain, posture, respiratory strength.